2006
DOI: 10.1097/01.pas.0000208899.15859.cb
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Involvement in Mantle Cell Lymphoma: A Prospective Clinic, Endoscopic, and Pathologic Study

Abstract: The frequency of gastrointestinal (GI) tract involvement in mantle cell lymphoma (MCL) at diagnosis is reported to be below 30%. To investigate the actual frequency of GI involvement by MCL, upper and lower endoscopy was prospectively performed on 13 untreated MCL patients at diagnosis. Multiple biopsies from endoscopically normal and abnormal gastric and colonic mucosa were studied with immunohistochemistry (IHC) for CD20, CD5, and cyclin D1, as well as fluorescence in situ hybridization (FISH) for t(11;14) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(74 citation statements)
references
References 40 publications
8
63
0
2
Order By: Relevance
“…46 Approximately 25% of patients with documented nodal mantle cell lymphoma have gastrointestinal symptoms, yet the lymphoma is present histologically in the lower gastrointestinal tract in 77% to 88% of patients and in the upper gastrointestinal tract in 43% to 77%. 51,52 Moreover, microscopic documentation of mantle cell lymphoma is reported in 84% of patients with normal visual findings by lower endoscopy and in 45% of patients with macroscopically normal findings by upper endoscopy. 51 Such examples can be histologically indistinguishable from focal lymphoid hyperplasia, but immunohistochemical stains, including nuclear cyclin D1 reactivity, confirm gastrointestinal involvement by mantle cell lymphoma.…”
Section: -46mentioning
confidence: 99%
“…46 Approximately 25% of patients with documented nodal mantle cell lymphoma have gastrointestinal symptoms, yet the lymphoma is present histologically in the lower gastrointestinal tract in 77% to 88% of patients and in the upper gastrointestinal tract in 43% to 77%. 51,52 Moreover, microscopic documentation of mantle cell lymphoma is reported in 84% of patients with normal visual findings by lower endoscopy and in 45% of patients with macroscopically normal findings by upper endoscopy. 51 Such examples can be histologically indistinguishable from focal lymphoid hyperplasia, but immunohistochemical stains, including nuclear cyclin D1 reactivity, confirm gastrointestinal involvement by mantle cell lymphoma.…”
Section: -46mentioning
confidence: 99%
“…The frequency of GI involvement in MCL has been previously underestimated, with previous reports citing 30% of MCL cases (by EGD and colonoscopy) [13]. But with more recent studies, GI tract infiltration has been shown in up to 92% of cases microscopically (from biopsies of lymphoid aggregates in normal and abnormal mucosae) [10]. Upper GI tract involvement is more common than colonic [6].…”
Section: Introductionmentioning
confidence: 99%
“…In our case, the polypoid lesions in the duodenum were most probably MLP. Recent reports have endoscopically revealed that 46%-49% of MCL patients had esophago-gastroduodenal involvement, and that 38%-62% had colorectal involvement [10,13]. Endoscopic findings of the upper and lower GI tract in MCL have included inflammation, nodules, polyps, ulcers, thickened walls, and masses [13].…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The patient's abdominal pain may be attributed to a lymphoproliferative process such as mantle cell lymphoma, which involves the gastrointestinal tract in the majority of cases. B symptoms are present in 30% of patients (8,9) and splenomegaly may be massive. Cytopenias are usually secondary to BM infiltration, typically seen in advanced disease.…”
Section: Malignancymentioning
confidence: 99%